Monocytes from depressed patients display an altered pattern of response to endotoxin challenge. - Lucia Lisi (Public Library of Science (PLoS), 2013)
It is now well established that major depression is accompanied and characterized by altered responses of the immune-inflammatory system. In this study we investigated the pro-inflammatory activation of monocytes isolated from depressed patients as a parameter not influenced by such confounds as the time of day, the nutritional and exercise status or the age and gender of patients. Monocytes from depressed patients and from healthy controls were isolated in vitro; after 24-h incubation under basal conditions, cells were exposed for 24-h to 100 ng/ml of endotoxin (bacterial lipopolysaccharide, LPS). We found that monocytes from drug-free depressed patients and controls release the same amounts of prostaglandin E2 (PGE2) under basal conditions, whereas monocytes from patients are dramatically less reactive to LPS (8.62-fold increase vs previous 24 hrs) compared to healthy controls (123.3-fold increase vs previous 24 hrs). Such blunted prostanoid production was paralleled by a reduction in COX-2 gene expression, whereas other pro-inflammatory mediators, namely interleukin-1β (IL-1 β) and -6 (IL-6) showed a trend to increased gene expression. The above changes were not associated to increased levels of circulating glucocorticoids. After 8 months of antidepressive drug treatment, the increase in PGE2 production after the endotoxin challenge was partially restored, whereas the increase in IL-1 β and -6 levels observed at baseline was completely abolished. In conclusion, our findings show that the reactivity of monocytes from depressed patients might be considered as a marker of the immune-inflammatory disorders associated to depression, although the lack of paired healthy controls at follow-up does not allow to conclude that monocyte reactivity to endotoxin is also a marker of treatment outcome.